Identitas Naratif Aktivis Perempuan: Rekonstruksi Pengalaman dan Orientasi dalam Gerakan Kesetaraan Gender di Bali - I Made Anom Wiranata; Penny Kurnia Putri (Universitas Udayana, 2021)
The struggle to change patriarchal ideology towards gender equality in Bali requires commitment, energy, and time. A number of women in Bali took positions and actions to be intensively engaged in the gender equality movement. The purpose of this research is to understand the narrative identity of gender equality activists in Bali. With phenomenology method, this study finds that the motivation to engage in the gender equality movement stems from the interpretation of personal observations on cases of discrimination and marginalization of women in their respective environments. This meaning becomes the basis of their identity as women activists. Political reforms and affirmative policies towards women are seen by them as opportunities to start taking part in or enlarging the gender equality movement. The meaning of self and value orientation underlies the choice to focus on the movement segment which includes gender education, legal case assistance, and socialization of gender equality norms.